A Novel Clustering-Based Scheme for Wildfire Monitoring in Flying Ad Hoc Networks - Visa, Samson Bitrus; Sunday, Caleb Gasin; Abdulkadir, Abubakar (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study addresses energy consumption limitations and network overhead in cluster formation within Flying Ad Hoc Networks (FANETs), a type of Wireless Sensor Network (WSN) commonly used for wildfire monitoring. FANETs consist of mobile nodes, represented by Unmanned Aerial Vehicles (UAVs), communicating in a self-organized manner, with clustering playing a crucial role in improving scalability and resource management. This work proposes an Energy Efficient Wildfire Monitoring Scheme (EEWMS) to optimize Cluster Head (CH) selection and reduce the energy costs of cluster formation. The scheme incorporates node remaining energy, trust level, energy consumption, base station proximity, mobility, and CH coverage into a fitness function for intelligent CH selection. EEWMS was validated through simulations in the MATLAB environment, comparing its performance against existing techniques, specifically EE-SS, using metrics including energy consumption, network lifespan, and cluster formation time. The results demonstrate that EEWMS significantly enhances FANET performance, reducing cluster building time by 10.16%, increasing cluster lifetime by 6.96% and improving energy efficiency by 10.25%. These improvements underscore EEWMS's effectiveness in enhancing real-time wildfire monitoring by improving network responsiveness, extending operational periods, and ensuring reliable data transmission. The findings provide a robust solution to energy and scalability challenges, making FANETs more efficient and reliable for emergency response applications.